1990
DOI: 10.1164/ajrccm/142.2.283
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Refeeding on Peripheral and Respiratory Muscle Function in Malnourished Chronic Obstructive Pulmonary Disease Patients

Abstract: We carried out a prospective randomized controlled trial to investigate the effects of short-term refeeding (16 days) in 10 malnourished inpatients with chronic obstructive pulmonary disease (COPD). Six patients were randomized to receive sufficient nasoenterically administered calories to provide a total caloric intake equal to 1,000 kcal above their usual intake. The other four patients were sham fed, receiving only 100 kcal more. Measurements of nutritional status, respiratory muscle strength and endurance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
71
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(75 citation statements)
references
References 6 publications
0
71
1
3
Order By: Relevance
“…1). Although this study suggested that diaphragm adaptation was of considerably less importance than previously suggested, it did not exclude its occurrence, as our results could have been obtained despite adaptation in other factors (for example diaphragm geometry, malnutrition [16], steroid use [17] or blood gas disturbances [18,19]) had reduced diaphragm strength. To further investigate whether adaptation occurs, we used another length-dependent property of muscle, specifically the fact that muscle shortening has a disproportionately detrimental effect on the tension (or pressure) elicited by low-frequency stimuli [20,21].…”
contrasting
confidence: 77%
“…1). Although this study suggested that diaphragm adaptation was of considerably less importance than previously suggested, it did not exclude its occurrence, as our results could have been obtained despite adaptation in other factors (for example diaphragm geometry, malnutrition [16], steroid use [17] or blood gas disturbances [18,19]) had reduced diaphragm strength. To further investigate whether adaptation occurs, we used another length-dependent property of muscle, specifically the fact that muscle shortening has a disproportionately detrimental effect on the tension (or pressure) elicited by low-frequency stimuli [20,21].…”
contrasting
confidence: 77%
“…Consequently, nutritional support has been advocated as a useful part of the care of COPD patients with low BMI. A number of nutritional intervention studies with pulmonary function, exercise capacity or weight increase as outcome have been performed [4][5][6][7]. However, a recent meta-analysis reviewed the effect of these studies and concluded that the studies did not document a beneficial effect of nutritional support in patients with COPD [8].…”
mentioning
confidence: 99%
“…For instance, following EN, hospitalized patients with COPD experienced improved maximal expiratory and inspiratory pressures. 45 Researchers identified improved immune function after EN was provided to other populations, such as elderly hospitalized patients and hospitalized patients with critical illness. 4,[46][47] Similarly, a meta-analysis identified functional benefits after EN for patients in the community with primary diagnoses including COPD, cystic fibrosis, GI disease, HIV, and cancer.…”
Section: Improved Outcomes Resulting From Enmentioning
confidence: 99%